2002
DOI: 10.1124/jpet.300.2.460
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Endotoxemia Augments Toxic Responses to Chlorpromazine: Is There a Relationship to Drug Idiosyncrasy?

Abstract: Idiosyncratic reactions occur in a small fraction (typically Ͻ5%) of the population taking therapeutic drugs. Chlorpromazine (CPZ) is a phenothiazine, antipsychotic drug that has caused several idiosyncratic responses during its therapeutic use. Clinical evidence suggests that conditions associated with inflammation are risk factors for the appearance of these responses. Accordingly, we tested the hypothesis that an inflammatory stimulus, bacterial lipopolysaccharide (LPS), renders animals susceptible to CPZ-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 37 publications
4
64
0
1
Order By: Relevance
“…These observations agrees with those of [16] in which animal model indicated such liver toxicity and he concluded that the effect is dose related and reproduceable.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These observations agrees with those of [16] in which animal model indicated such liver toxicity and he concluded that the effect is dose related and reproduceable.…”
Section: Discussionsupporting
confidence: 82%
“…The method described by [16] was used to determine body weight of experimental rats. Individual rat was monitored for daily gain in body weight using digital electronic balance (Gilbertini, Italy).…”
Section: Determination Of Body Weightmentioning
confidence: 99%
“…Similarly, the extent of liver injury induced by chlorpromazine (CPZ), a psychotropic drug which has been associated with idiosyncratic cholestatic liver injury, is greatly potentiated by concomitant administration of LPS (Buchweitz et al, 2002). Thus, pretreatment of rats with low doses of LPS, followed by injection of a non-toxic dose of CPZ, caused elevations of plasma aminotransferase activities and increases in the number of hepatic neutrophils.…”
Section: Lps Modelmentioning
confidence: 99%
“…Chlorpromazine (CPZ) is a phenothiazine antipsychotic drug associated with IDILI in humans, and coexposure of rats to CPZ and LPS precipitates liver injury (Buchweitz et al, 2002). Exposure of mice or primary murine hepatocytes to CPZ combined with LPS or the Toll-like receptor 2 agonist lipoteichoic acid resulted in hepatocellular injury that was associated with prolonged JNK activation (Gandhi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among several hypotheses put forth to explain IDILI is the inflammatory stress hypothesis, which states that a mild inflammatory episode interacts with a drug, resulting in hepatotoxicity (Shaw et al, 2010). Animal models based on this hypothesis have been developed for several drugs that have caused IDILI in humans, including chlorpromazine, ranitidine, amiodarone, doxorubicin, sulindac, and trovafloxacin (TVX) (Buchweitz et al, 2002;Luyendyk et al, 2003;Shaw et al, 2007;Hassan et al, 2008;Zou et al, 2009;Lu et al, 2012). In each of these models, bacterial lipopolysaccharide (LPS) was used to cause a modest, nontoxic, acute inflammatory episode.…”
Section: Introductionmentioning
confidence: 99%